2019
DOI: 10.1098/rspb.2019.0588
|View full text |Cite
|
Sign up to set email alerts
|

Sociality emerges from solitary behaviours and reproductive plasticity in the orchid beeEuglossa dilemma

Abstract: The evolution of eusociality and sterile worker castes represents a major transition in the history of life. Despite this, little is known about the mechanisms involved in the initial transition from solitary to social behaviour. It has been hypothesized that plasticity from ancestral solitary life cycles was coopted to create queen and worker castes in insect societies. Here, we tested this hypothesis by examining gene expression involved in the transition from solitary to social behaviour in the orchid bee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 41 publications
2
52
0
1
Order By: Relevance
“…In social subordinate females, surprisingly, functions related to egg production were upregulated in young individuals. Subordinate females of this species, unlike sterile workers of highly eusocial species, have been reported to lay eggs, although the dominant female systematically replaces subordinate eggs with her own ( Saleh and Ramírez 2019 ). Other pathways which were enriched among age-related genes in subordinate females were mainly linked to metabolism (e.g., lipid metabolic process, fructose 6-phosphate metabolic process), which may reflect the metabolically costly behaviors carried out by this caste (foraging and nest defense, Boff et al 2015 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In social subordinate females, surprisingly, functions related to egg production were upregulated in young individuals. Subordinate females of this species, unlike sterile workers of highly eusocial species, have been reported to lay eggs, although the dominant female systematically replaces subordinate eggs with her own ( Saleh and Ramírez 2019 ). Other pathways which were enriched among age-related genes in subordinate females were mainly linked to metabolism (e.g., lipid metabolic process, fructose 6-phosphate metabolic process), which may reflect the metabolically costly behaviors carried out by this caste (foraging and nest defense, Boff et al 2015 ).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, these functions were upregulated with age, suggesting that solitary females invest more in somatic repair as they get older. This may reflect the shift in behavior which solitary females undergo with age in this species, as young foundress females may invest more in reproduction and metabolically costly tasks related to nest construction, whereas older solitary females are primarily guarding their brood inside the nest ( Saleh and Ramírez 2019 ) and may therefore be able to invest more in somatic maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Genes relating to metabolic activities appear to be upregulated in young rather than old solitary females, suggesting that high metabolic activity early in life may increase senescence, as predicted by the free radical theory of ageing (Harman 1982). In the cryptic sister species Euglossa dilemma, young foundress females indeed spend more time foraging for brood provisions, a metabolically costly task, compared to when they later enter the "guard phase", during which they stay in the nest, guarding their brood cells (Saleh and Ramírez 2019). Interestingly, genes directly related to the oxidative metabolism of various substrates, notably lipids (cytochrome P450, cytochrome b5) are upregulated with age in solitary females.…”
Section: Overlap Of Age-related Genes Between the Differential Gene Ementioning
confidence: 91%
“…Another factor which may explain the lack of ageing signs in dominant females is the ingestion of subordinate-laid eggs by dominant females. Video recordings of E. dilemma nests revealed that oophagy, whereby the dominant female ingests eggs laid by subordinate females in her nest to replace them with her own, occurs commonly in this species (Saleh and Ramírez 2019). If this behaviour also occurs in the closely related E. viridissima, this could constitute a notable nutritional source for dominant females, thereby reducing any trade-off generated by the allocation of limited resources.…”
Section: ) Silencing Of Transposable Elementsmentioning
confidence: 97%
See 1 more Smart Citation